ALUR TOKOH DAN PENOKOHAN LATAR NOVEL DAN FILM ANCIKA DIA YANG BERSAMAKU KAJIAN EKRANASI - Winda Waromah; Helmi Seftiani; Dwi Setiyawan (CV. Denasya Smart Publisher, 2025)
This research explores the process of ekranisasi the adaptation of literary works into cinematic form through a comparative analysis of the novel